Pain management in photodynamic therapy using a nitrous oxide/oxygen mixture: a prospective, within-patient, controlled clinical trial - Müller-Christmann, Christine; Uhlmann, Lorenz; Enk, Alexander; Gholam, Patrick (Journal of the European Academy of Dermatology and Venereology, 2017)
Background Photodynamic therapy is an effective treatment for actinic keratoses. Nevertheless, severe pain during the procedure is a serious adverse effect, which leads to interruption or even termination. Complete pain relief remains a difficult challenge. Objective To evaluate the effect of a nitrous oxide/oxygen mixture on pain intensity during photodynamic therapy. Methods This clinical trial has been designed as a prospective, single-centre, explorative, controlled, observational study. Results We were able to detect a significant overall pain reduction of 55.2% after application of a nitrous oxide/oxygen mixture by means of an intra-individual comparison. Furthermore, the total number of therapy interruption significantly decreased by 82% after the inhalation analgesia. Additionally, treatment satisfaction ranged from ‘extremely to very satisfied’. Conclusions This study shows that analgesia by means of a nitrous oxide/oxygen mixture is a very effective and well-tolerated method for achieving significant pain reduction during photodynamic therapy.